A novel method of measuring passive quasi-stiffness in the first metatarsophalangeal joint. Issue 1 (December 2016) - Heng, Marabelle; Chua, Yaohui; Pek, Hong; Krishnasamy, Priathashini; Kong, Pui
Abstract Background First metatarsophalangeal joint (MTPJ) mobility is commonly assessed by its angular displacement (joint angle) or subjectively rated as 'hypermobile', 'normal' or 'stiff' by a clinician. Neither of these methods is ideal because displacement alone does not take into account the force required to displace the joint and subjective evaluation is not always reliable. This study presented a novel method to determine the passive quasi-stiffness of the first MTPJ. The reliability of the proposed method was also assessed. The first MTPJ passive quasi-stiffness of 13 healthy subjects were measured at two occasions, 7 days apart, by two testers (experienced and inexperienced). A tactile pressure sensing system was used to measure the force applied to dorsiflex the first toe by the testers. The torque (in Nmm) about the first MTPJ was calculated as the applied force (in N) multiplied by a moment arm (in mm), where moment arm was the length of the first proximal phalanx. A video camera recorded the motion of the first MTPJ, simultaneously with force measurements, to determine the joint angular displacement (in degrees) using the Dartfish software. The quasi-stiffness (in Nmm/degrees) was calculated as the slope of a graph where torque was plotted against first MTPJ angular displacement. Descriptive statistics of the first MTPJ quasi-stiffness were calculated. Intra-rater and inter-rater reliability were assessed using Bland and Altman plot, intraclass correlation coefficients (ICC), and standard error of measurement (SEM). Results First MTPJ quasi-stiffness of the subjects ranged widely from 0.66 to 53.4 Nmm/degrees. Intra-rater reliability for experienced tester was moderate (Session 1: 14.9 ± 14.6 Nmm/degrees, Session 2: 14.2 ± 8.5 Nmm/degrees, ICC = .568, SEM = 7.71 Nmm/degrees). Inter-rater reliability between experienced (12.6 ± 8.4 Nmm/degrees) and non-experienced (19.9 ± 9.2 Nmm/degrees) testers was poor (ICC = -.447, SEM = 11.29 Nmm/degrees). Conclusions First MTPJ passive quasi-stiffness can be quantified from torque and angular displacement measurements using simple equipment in a clinical setting. The tester's experience affected the consistency in joint quasi-stiffness measurements.